2009
DOI: 10.1210/jc.2008-2093
|View full text |Cite
|
Sign up to set email alerts
|

Progestins Activate the AKT Pathway in Leiomyoma Cells and Promote Survival

Abstract: The progestin, R5020, can rapidly activate the AKT pathway. Inhibition of the AKT pathway inhibits cell proliferation and promotes apoptosis of leiomyoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 34 publications
1
47
0
3
Order By: Relevance
“…They also demonstrated that progesterone upregulates expression of proliferating cell nuclear antigen (PCNA) and epidermal growth factor (EGF), both are known regulators of leiomyoma cellular proliferation (58,59). Furthermore, Hoekstra and colleagues (60) demonstrated that R5020 (a synthetic progestin that acts as an agonist of progesterone receptors) induces proliferation of leiomyoma cells in vitro. In addition, they found that R5020 activates (through phosphorylation) AKT and glycogen synthase kinase-3B (GSK3B).…”
Section: Progesteronementioning
confidence: 99%
“…They also demonstrated that progesterone upregulates expression of proliferating cell nuclear antigen (PCNA) and epidermal growth factor (EGF), both are known regulators of leiomyoma cellular proliferation (58,59). Furthermore, Hoekstra and colleagues (60) demonstrated that R5020 (a synthetic progestin that acts as an agonist of progesterone receptors) induces proliferation of leiomyoma cells in vitro. In addition, they found that R5020 activates (through phosphorylation) AKT and glycogen synthase kinase-3B (GSK3B).…”
Section: Progesteronementioning
confidence: 99%
“…Progesterone-bound PR dimers are translocated to the nucleus, bind to DNA, recruit cofactors, and induce B-cell lymphoma 2 (Bcl-2) gene expression [12] in a so-called genomic signaling pathway. Discovered some time later, non-genomic (purely cytoplasmic) signaling of PR regulates Akt pathway activation [13]. …”
Section: Introductionmentioning
confidence: 99%
“…PI3K generates phosphatidylinositol-(3,4,5)-triphosphate (PIP3), which in turn activates 3-phosphoinositide-dependent protein kinase 1 (PDK1). PDK1 then activates protein kinase B (PKB/Akt) [16,17]. Apoptosis signaling involves cysteine aspartate-specific protease (caspase)-dependent and -independent apoptosis.…”
Section: Introductionmentioning
confidence: 99%